Comparison of Measured Soft X-Ray Yield Versus Pressure for NX1 and NX2 Plasma Focus Devices Against Computed Values Using Lee Model Code - Gautam, P.; Khanal, R.; Saw, S. H.; Lee, S. (Springer US, 2015)
The soft X-ray yield versus pressure curves of NX1 and NX2 plasma focus machines have been measured and published for different pressures and electrode configurations. In this work, the numerical experiments are carried out, using Lee model code. The Lee model code is configured for each of these devices NX1 and NX2 by fitting computed total discharge current waveform against a measured total discharge current waveform. The computed soft X-ray yield versus pressure curves are compared with the laboratory measured soft X-ray yield versus pressure data. The comparison shows agreement between computation and measurement of several important features of the yield versus pressure curves.